Socio-Economic Marginalization and Compliance Motivation Among Students and Freeters in Japan - Liu, I-Ting Huai-Ching; Uchida, Yukiko; Norasakkunkit, Vinai (Frontiers in Psychology, 2019)
This study examines the compliance motivation of students and Freeters when facing a marginalization-risk situation evoked by priming. Freeter (part-time employers), NEET (not in education, employment, or training) and Hikikomori (social withdrawal) represent the socio-economically marginalized population in Japan. People at higher risk of becoming NEET and Hikikomori have shown a motivation pattern deviant from mainstream Japanese culture, including lower willingness to conform to in-group members, thus showing less cultural fit (Norasakkunkit & Uchida, 2014). In this study we explore the effect of the macro socio-economic situation (job-hunting prospects being good or bad) on individual’s compliance motivation in both students and Freeters. 65 Kyoto University students and 74 Freeters were randomly assigned to one of the two priming conditions (marginalization-risk or non-marginalization) before completing the NEET-Hikikomori Risk (NHR) scale and measurements of compliance motivation to conform to in-group members or to be self-consistent (Cialdini et al., 1999). 23 control group students and 22 control group Freeters were also recruited online for comparison. Results showed that marginalization-risk priming led to lower tendency to be self-consistent among students, but did not lead to lower tendency to conform to in-group members. For Freeters, marginalization-risk priming led to higher compliance motivation to conform to in-group members. The results confirmed the framework proposed by Toivonen, Norasakkunkit and Uchida (2011) that both Freeters and students in Japan have ritualist reactions, continuing to maintain the cultural norms despite the difficulty of attaining the cultural goals.